Elements and materials improve the FDM products: a review - Bala, Abduladim Salem; Wahab, Saidin; Ahmad, Mazatusziha (Trans Tech Publication Ltd, 2016)
This work aims to provide a review of available published literature that explores the opportunities to improve the quality of fused deposit modelling (FDM) products, particularly in medical applications. The paper presents details concerning the basis of the technology, process parameter settings and their responses, and reviews the properties of common FDM engineering/bio-materials and the available methods applied for improving their performance. Based on the researches which have been reviewed, FDM technology development is based on three elements namely; raw material, process parameters settings, and slicing software. The present paper deals with the first two elements owing to their importance. FDM works within a complex environment from process parameters. Thus it can achieve good results only with the proper settings for these parameters according to the properties of the material used. Improving the polymers is essentially based on the correct selection of additive materials, which can particularly enhance the key property/properties in the matrix material. This review provides a brief insight into FDM technology, a clear idea for the process parameter settings, available/suggested materials and ways of modifying their properties to consequently improve the quality of FDM products.